Assessing Nutrient Leaching Loss Using Nonweighing Lysimeters in Acidic Soils of Eastern Plateau and Hill Region of India. Issue 9 (15th May 2021) - Naik, Sushanta Kumar; Mali, Santosh Sambhaji; Kumar, Omkar; Singh, Arun Kumar; Bhatt, Bhagwati Prasad
ABSTRACT: Leaching losses of nutrients in the winter crops of tomato and pea cultivated in acidic soils of the eastern plateau and hill region were studied using nonweighing type lysimeters under different nutrient management practices involving the control (T1 ), inorganic (T2 ), organic (T3 ), and integrated (organic + inorganic, T4 ) sources of nutrients. The leaching loss of nutrients varied significantly among various fertilizer management practices and the rate of loss differed among the nutrients. The treatment receiving 100%-recommended dose of NPK as inorganic form (T2 ) recorded highest N, and K leaching loss of 22.1, 14.8 kg ha −1 in tomato accounting 13.7% and 21.1% of the applied fertilizer, while in pea, it was 9.14 and 10.8 kg ha −1, respectively, accounting 20.3% and 20.4% of the applied fertilizer. The P-leaching loss was comparatively less and the differences among the treatments were statistically nonsignificant. The fruit yield of tomato was significantly highest (44.8 t ha −1 ) in the treatment with integrated fertilizer sources (T4 ), which was 52.7% higher over control (T1 ). The pod yield of pea was highest (11.3 t ha −1 ) in T3 and was 59.7% higher over control.